2019
DOI: 10.1111/prd.12283
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hyperglycemia as a risk factor in implant therapy

Abstract: It has been estimated that by 2030, the number of patients with diabetes aged > 64 years will be > 82 million in underdeveloped countries, and > 48 million in developed countries. Chronic hyperglycemia delays wound healing by reducing the expression of growth factors in the wound fluid and re‐epithelialization. Impaired wound healing in patients with diabetes has also been associated with inhibition of the production of stromal cell‐derived factor‐1alpha by several tissues including bone marrow, brain, heart, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 50 publications
0
43
0
Order By: Relevance
“…Furthermore, some studies have reported that hyperglycemia can inhibit epithelium cell proliferation and migration. These phenomena may inhibit wound healing and lead to the formation of wounds [35]. The three types support and protect each other.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies have reported that hyperglycemia can inhibit epithelium cell proliferation and migration. These phenomena may inhibit wound healing and lead to the formation of wounds [35]. The three types support and protect each other.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors influencing the healing and prognosis of dental implants, such as smoking and diabetes mellitus, have been extensively discussed in the literature and have also been reported in the present volume of Periodontology 2000 by Javed et al. Tobacco smoking and habitual use of nicotine‐related products, as environmental risk factors in implant therapy, and the effect of nicotine on osseointegration, have been also discussed .…”
Section: Systemic Factors Affecting Implant Prognosismentioning
confidence: 78%
“…These phenomena may inhibit wound healing and lead to the formation of wounds (35). The three types support and protect each other.…”
Section: Discussionmentioning
confidence: 99%